Effect of pharmacist-led interventions on blood pressure among asult Asian patients with hypertension: A systematic review and meta-analysis - Delgado, Shevvie Belle L.; Guinto, Mikaela Gail M.; Hawili III, Arnold Armando; Gloria, Mac Ardy J. (Manila: Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2024)
Background: With the expanding role of pharmacists in patient-centered care, studies and reviews investigate its effectiveness in hypertension management; however, results show inconsistency and less generalizability in the Asian population.

Objectives: We aim to determine the effect of pharmacist-led interventions to the blood pressure of adult Asian patients with hypertension in comparison to no pharmacist-led intervention.

Methods: Systematic review of PubMed, Scopus, EBSCO, Web of Science, Wiley, grey literature, and hand search was conducted from inception to September 2023. Inclusion criteria specified randomized controlled trials with adult Asian patients with hypertension receiving pharmacist-led intervention compared with no pharmacist-led intervention, and reported change in systolic and diastolic blood pressure (SBP & DBP) with no language restrictions. Study quality was assessed through Cochrane Risk of Bias tool, with results analyzed qualitatively and quantitatively in accordance with PRISMA guidelines. Meta- analysis using random-effects model was conducted, heterogeneity checked through I* statistics and its sources explored through subgroup analysis. Funnel plot was generated to assess publication bias.

Results: Of the 11,914 studies, 14 containing 2,945 participants were analyzed. Predominant intervention investigated was educational intervention. Pharmacist-led interventions significantly decreased SBP by -5.15 mmHg (95%CI -8.43 to -1.88) and DBP by -2.59 mmHg (95%CI -4.85 to -0.32). Subgroup analysis revealed healthcare setting, number of interventions investigated, non-use of technology, predominant sex, country income status, and prevailing level of education affect SBP and DBP lowering; age group affected SBP, and frequency of follow-up and timeframe affected DBP. Quality assessment revealed high risk of bias. Publication bias was present for DBP.

Conclusion: Analysis showed pharmacist-led interventions can significantly reduce blood pressure of adult Asian patients with hypertension compared to no pharmacist-led intervention. Interpret findings with caution due to heterogeneity, risk of bias, and publication bias. The findings support optimization of hypertension management via pharmacist-led interventions.
Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Manila, June 2024
Keywords: Hypertension -- Treatment; Blood pressure -- Regulation; Pharmacist and patient; Systematic reviews (Medical research); Meta-analysis.; Asians -- Health and hygiene; Patient care management; Health outcomes assessment; Pharmacist-led intervention